Human CD8 T cells are susceptible to TNF-mediated activation-induced cell death - Otano, Itziar (Theranostics, 2020)
Activation-induced cell death (AICD) is a complex immunoregulatory mechanism that causes the demise of a fraction of T-lymphocytes upon antigen-driven activation. In the present study we investigated the direct role of TNF in AICD of CD8 T lymphocytes. Methods: Human peripheral mononuclear cells were isolated from healthy donors and fresh tumor-infiltrating lymphocytes were obtained from cancer patients undergoing surgery. T cells were activated with anti-CD3/CD28 mAbs or with a pool of virus peptides, in combination with clinical-grade TNF blocking agents. Results: A portion of CD8 T cells undergoes apoptosis upon CD3/CD28 activation in a manner that is partially prevented by the clinically used anti-TNF agents infliximab and etanercept. TNF-mediated AICD was also observed upon activation of virus-specific CD8 T cells and tumor-infiltrating CD8 T lymphocytes. The mechanism of TNF-driven T cell death involves TNFR2 and production of mitochondrial oxygen free radicals which damage DNA. Conclusion: The use of TNF blocking agents reduces oxidative stress, hyperpolarization of mitochondria, and the generation of DNA damage in CD8 T celss undergoing activation. The fact that TNF mediates AICD in human tumor-reactive CD8 T cells suggests that the use of TNF-blocking agents can be exploited in immunotherapy strategies.